2020
DOI: 10.26633/rpsp.2020.81
|View full text |Cite
|
Sign up to set email alerts
|

Coping with being cooped up: Social distancing during COVID-19 among 60+ in the United States

Abstract: Objectives. This study examined the impact of sheltering in place and social distancing among adults aged 60 and older during the 2020 outbreak of COVID-19 in the United States. Methods. Using convenience sampling respondents were asked to complete a web-administered survey to explore impact of social distancing on loneliness, stress, and behavioral changes. The analytic sample consisted of 833 responses of persons aged 60 and older. Results. A large portion reported being stressed (36%), and/or being lonely (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
86
1
19

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(118 citation statements)
references
References 7 publications
8
86
1
19
Order By: Relevance
“…The studies here reviewed also highlight how healthy older adults forced to isolate socially reported high levels of stress (21), anxiety and depression that seem to be particularly associated with loneliness (22). Similarly, worsening or emergence of new neuropsychiatric symptoms was found in a substantial proportion (about 25-60%) of patients with cognitive decline as a result of social isolation (23,24), although changes in symptom severity were found to be similar between patients with mild cognitive impairment and dementia (26).…”
Section: Neuropsychiatric Symptoms In People In Social Isolation Duementioning
confidence: 85%
See 2 more Smart Citations
“…The studies here reviewed also highlight how healthy older adults forced to isolate socially reported high levels of stress (21), anxiety and depression that seem to be particularly associated with loneliness (22). Similarly, worsening or emergence of new neuropsychiatric symptoms was found in a substantial proportion (about 25-60%) of patients with cognitive decline as a result of social isolation (23,24), although changes in symptom severity were found to be similar between patients with mild cognitive impairment and dementia (26).…”
Section: Neuropsychiatric Symptoms In People In Social Isolation Duementioning
confidence: 85%
“…Seven studies focussed on investigating the impact that social isolation due to COVID-19-related restrictions had on neuropsychiatric symptoms of older adults with (23)(24)(25)(26)(27) and without dementia (21,22). Only one single case (27) and one case series (25) were described, while all the other studies used surveys/questionnaires implemented either via online (21,22) or telephonic (23,24,26) administration. The majority of these studies included standardised tools to assess the presence and severity of neuropsychiatric symptoms, mostly the Neuropsychiatric Inventory (NPI) (23,26,27).…”
Section: Individuals Without Covid-19 Infection In Conditions Of Incrmentioning
confidence: 99%
See 1 more Smart Citation
“…First studies investigating coping with the pandemic – though again not focusing on older individuals – reported that proactive coping behaviors, such as social activities (e.g. sharing worries with others, using social media to keep in touch with others), a healthy diet, physical activity, keeping a routine and pursuing hobbies were associated with better mental wellbeing [ 12 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…22 Living alone is as an important risk factor for loneliness, both pre-COVID-19 4,28,29 and presently. 27,30,31 We found that living alone predicted loneliness in women and men, although the effect was greater in men.…”
Section: Discussionmentioning
confidence: 67%